A Hybrid Chinese National Cryptographic Algorithm Based Solution for Data Encryption and Decryption in Transmission - WANG Jinquan; DENG Jian; HE Hongjie (Kongzhi Yu Xinxi Jishu)
In a vehicle intelligent operation and maintenance system, the ground data processing platform needs to collect vehicle operational status data in real time for vehicle monitoring and health status analysis. To ensure the security of the transmitted data, this paper proposes a secure data transmission solution based on the application scenario of in-vehicle status data transmission, combining the features of chinese national cryptographic algorithms SM4 and SM9.This solution utilizes SM4 to achieve fast encryption of the plaintext in-vehicle status data, ensuring the confidentiality, integrity, resistance to attacks, and resistance to interference of the data. Additionally, SM9 is used to encrypt the key transmission of SM4, ensuring the confidentiality, resistance to attacks, and non-repudiation of the keys. Experimental results show that compared with other solutions, the proposed solution not only guarantees the integrity, confidentiality and non-repudiation of vehicle-to-ground data transmission, but also exhibits good versatility and high efficiency. It is applicable for various types of vehicles, data processing platforms and communication network environments, featuring high throughput, low resource consumption and extensive application in the future.